Literasi Internet Solusi Atasi Budaya Cyberbullying di Kalangan Remaja - Khoerunnisa, Lutfi; Anwar, Rully Khairul; Siti Khadijah, Ute Lies (Ilmu Informasi Perpustakaan dan Kearsipan, 2021)
The internet is a dish of technological innovation today. Cyberbullying is a network-based bullying crime by utilizing internet media. Cyberbullying is more experienced by teenage children below the age of 18 years. This study aims to determine the role of internet literacy in overcoming cyberbullying cases. This research uses descriptive qualitative method with literature study approach. The results of this study indicate the ability of internet literacy can be a real solution in preventing cyberbullying. Internet literacy education can be applied in formal institutions that are aligned with computer science subjects where students are not only able to operate but are also able to use the internet wisely, properly and correctly as a medium to meet the information needs and supporting communication media among humans.